Post-Pandemic Economic Recovery of Village Communities in SME Sectors through Night Markets - Anang R. Jatmiko; M. Fathurroman; Khoiruddin .; Hasanuddin .; Thomson Pranggono (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
This study aims to investigate the effects of village community's economic recovery on SME sectors in the post-pandemic era in Gudo District, Jombang Regency. A qualitative research was descriptively employed as the methodology approach. The investigation period began between February and April of 2022. The subjects were night market vendors who sold products on the street. By the snowball sampling method, the subjects were randomly selected. In this investigation, the data analysis techniques consisted of three steps: data reduction, data display, and conclusion drawing. The study found that the effects of the economic recovery of village communities on the SME sectors in the post-pandemic era in the Gudo district have a positive results by reducing or providing a solution to the number of unemployed and generating economic income for the Original Local Government Revenue. The negative effects included the addition of refuse and security measures, as well as unequal the Original Local Government Revenue income and expenditures for night market facilities.